Virtual Reality and Gamification for Promoting Physical Activity in Children: A Systematic Review of Current Trends and Innovations - Ramadan, Gilang; Sumaryanti, Sumaryanti; Nugroho, Sigit (Physical Education Theory and Methodology, 2026)
Background. Physical inactivity among children has risen globally, driven by sedentary behaviors and technology-mediated lifestyles. Emerging research suggests that virtual reality (VR) and gamification may serve as effective digital interventions for promoting physical activity (PA) and improving children’s health outcomes. Objectives. This systematic review aimed to synthesize and critically evaluate the current evidence on VR- and gamification-based interventions designed to promote PA among children, with a focus on intervention characteristics, theoretical mechanisms, effectiveness, and implementation considerations. Methods. Peer-reviewed studies were retrieved from Scopus, ERIC, and the ACM Digital Library. Eligible studies included intervention research involving children and adolescents aged 5–18 years that applied VR, exergaming, or gamified digital interventions to promote PA or related health outcomes. Data were extracted and synthesized according to intervention typology, theoretical underpinnings, outcomes, and implementation features. Results. The review included 11 intervention studies published between 2021 and 2025. Overall, VR- and gamification-based interventions demonstrated positive effects on PA engagement, motor outcomes, and selected psychosocial indicators. Effective designs commonly integrated goal setting, feedback, social comparison, and reward mechanisms, often aligned with Self-Determination Theory and Social Cognitive Theory. Key implementation barriers included cost, accessibility, and staffing requirements, while facilitators involved remote delivery models, stakeholder engagement, and the use of consumer-level hardware. Conclusions. VR and gamification hold significant potential for promoting children’s PA when interventions are theoretically grounded and well implemented. However, evidence for long-term effectiveness, sustainability, and equitable access remains limited, underscoring the need for longitudinal research and scalable, inclusive intervention models.